High-performance hierarchical graphene/metal-mesh film for optically transparent electromagnetic interference shielding. (May 2017) - Han, Yu; Liu, Yuxuan; Han, Lin; Lin, Jie; Jin, Peng
Abstract: This work first demonstrates the improved electromagnetic interference (EMI) shielding performance of monolayer graphene on highly transparent metal-meshes of random pattern. Metal-meshes are fabricated on quartz substrate by lift-off based on self-cracking template and CVD graphene is directly transferred onto thin metal-meshes to construct the hierarchical graphene/metal-mesh film, by which considerable improvements both in microwave reflection and absorption can be realized in thin metal-meshes. The shielding effectiveness (SE) of the hierarchical film even exceeds the summation of those of the monolayer graphene and the metal-mesh film. Detailed analyses reveal that absorption dominates the improvement in SE for a graphene/50 nm Ag-mesh film, with a three-fold absorption coefficient as well as a slightly increased reflectivity compared to the Ag-mesh itself. The as-prepared hierarchical film primely inherits the excellent optical transmission properties from random-pattern metal-meshes with high transmittance in visual-IR spectrum, low haze and faint diffraction. Moreover, the chemical stability of metal-meshes is highly improved with the protection of graphene. We anticipate that the hierarchical graphene/metal-mesh film can be a promising material to play a great role in realization of high-performance EMI shielding in emerging optoelectronic devices such as touch panels, displays, airborne optoelectronic pods, and aviation camcorders. Graphical abstract: